2015
DOI: 10.1104/pp.15.01347
|View full text |Cite
|
Sign up to set email alerts
|

SUPPRESSOR OF APICAL DOMINANCE 1 of Sporisorium reilianum Modulates Inflorescence Branching Architecture in Maize and Arabidopsis

Abstract: The biotrophic fungus Sporisorium reilianum causes head smut of maize (Zea mays) after systemic plant colonization. Symptoms include the formation of multiple female inflorescences at subapical nodes of the stalk because of loss of apical dominance. By deletion analysis of cluster 19-1, the largest genomic divergence cluster in S. reilianum, we identified a secreted fungal effector responsible for S. reilianum-induced loss of apical dominance, which we named SUPPRESSOR OF APICAL DOMINANCE1 (SAD1). SAD1 transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
37
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 57 publications
0
37
0
1
Order By: Relevance
“…These A. thaliana plants were bushier after eight weeks of growth due to increased secondary branching. 6 This demonstrated that GFP-SAD1 is able to affect the inflorescence branching pattern of transgenic A. thaliana without the aid of other fungal proteins. Here we present evaluations of time course experiments in S. reilianum-infected maize and transgenic A. thaliana plants in order to study the temporal dynamics of developmental changes.…”
mentioning
confidence: 93%
See 3 more Smart Citations
“…These A. thaliana plants were bushier after eight weeks of growth due to increased secondary branching. 6 This demonstrated that GFP-SAD1 is able to affect the inflorescence branching pattern of transgenic A. thaliana without the aid of other fungal proteins. Here we present evaluations of time course experiments in S. reilianum-infected maize and transgenic A. thaliana plants in order to study the temporal dynamics of developmental changes.…”
mentioning
confidence: 93%
“…Analysis of maize plants that were infected by S. reilianum, lacking or expressing SAD1, indicated that SAD1, even though expressed in every colonized plant tissue, 6 has an effect only on female inflorescences. At the female inflorescence, SAD1 manipulates bud outgrowth and induces growth of subapical ears.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequently, fungal hyphae proliferate inside the apoplast and/or grow through host cells, establishing an intimate contact zone for the exchange of nutrients and proteins. Functional genomic analyses of the grass smut fungi U. maydis, Sporisorium reilianum and U. hordei have greatly contributed to our understanding of smut infection and the associated host responses (K€ amper et al, 2006;Brefort et al, 2009;Ghareeb et al, 2015;Lanver et al, 2018). In short, these studies have revealed different repertoires of conserved and host-adapted effector proteins (Okmen & Doehlemann, 2014;Lanver et al, 2017).…”
Section: Introductionmentioning
confidence: 99%